Volume 4: 20th Design for Manufacturing and the Life Cycle Conference; 9th International Conference on Micro- And Nanosystems 2015
DOI: 10.1115/detc2015-46322
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Eco-Industrial Parks

Abstract: An eco-industrial park is a set of businesses that share resources in order to increase profitability and reduce environmental impact. The implementation of eco-industrial parks may significantly contribute to the creation of a sustainable economy. Despite this prospect, the actual development of eco-industrial parks is challenging, as a variety of factors must be considered. Not only technical, economic, and environmental factors are relevant but numerous stakeholder relationships as well, such as between fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
(66 reference statements)
0
10
0
4
Order By: Relevance
“…(Chertow, 2000) According to Deutz (2014), an industrial symbiosis is "a flow of underutilised resource(s) (comprising substances and/or objects and/or energy), from an entity which would otherwise discard them, to another entity which uses them as a substitute for new resources." The potential benefits of a symbiosis can be economical, environmental, and societal (Hein, Jankovic, Farel, & Yannou, 2015;Hellweg & Canals, 2014). Industrial symbiosis is a "collective approach" based on collaboration (Chertow, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…(Chertow, 2000) According to Deutz (2014), an industrial symbiosis is "a flow of underutilised resource(s) (comprising substances and/or objects and/or energy), from an entity which would otherwise discard them, to another entity which uses them as a substitute for new resources." The potential benefits of a symbiosis can be economical, environmental, and societal (Hein, Jankovic, Farel, & Yannou, 2015;Hellweg & Canals, 2014). Industrial symbiosis is a "collective approach" based on collaboration (Chertow, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…What we also need to know is which parameters are key for specific types of plants in order to link the parameters of the correlation with the key plant parameters. This is established by so-called plant meta-models, which were introduced in (Hein et al, 2015a(Hein et al, , 2015b. The plant meta-models are therefore a priori classifications of a certain plant within an industrial zone.…”
Section: Model Of Industrial Zonementioning
confidence: 99%
“…Paper 1 provided an example of this. The study of two existing excess heat collaborations consisted of spontaneously developed collaborations, which are held to be more functional, long-term and durable than planned attempts to create interorganisational collaborations (see, e.g., Chertow, 2007;Gibbs and Deutz, 2007;Baas, 2011;Ashton and Bain, 2012;Hein et al, 2015). Despite the fact that the development of the two studied cases differed, there were many similarities in terms of perceived drivers and barriers behind them.…”
Section: Important Key Elements Of Interorganisational Business Modelsmentioning
confidence: 99%
“…Regardless of the driving forces behind the development of such synergies, interorganisational collaborations in line with industrial symbiosis have been shown to result in significant financial and environmental benefits both for the companies involved and society at large (Hein et al, 2015;Hellweg and Canals, 2014;Doménech and Davies, 2009;Park and Behera 2015;Nicolas et al 2015;Deutz and Gibbs, 2008;Chertow, 2000;Şenlier and Albayrak, 2011). The benefits are connected to sustainable use of natural resources, collaborations on local resource potentials leading to increased productivity and increased urban quality, and so forth (Şenlier and Albayrak, 2011).…”
Section: Industrial Symbiosismentioning
confidence: 99%
See 1 more Smart Citation